2014
DOI: 10.1111/ahg.12055
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Screening of theHGDGene Identifies a Novel Alkaptonuria Mutation with Significant Founder Effect and High Prevalence

Abstract: SummaryAlkaptonuria (AKU) is an autosomal recessive disorder; caused by the mutations in the homogentisate 1, 2-dioxygenase (HGD) gene located on Chromosome 3q13.33. AKU is a rare disorder with an incidence of 1: 250,000 to 1: 1,000,000, but Slovakia and the Dominican Republic have a relatively higher incidence of 1: 19,000. Our study focused on studying the frequency of AKU and identification of HGD gene mutations in nomads. HGD gene sequencing was used to identify the mutations in alkaptonurics. For the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…[6][7][8] Some of the reported HGD variants are spread throughout the world, such as c.175delA (p.(Ser59Alafs*52)), one of the first identified AKU mutations, c.899T4G (p.(Val300Gly)). 7 On the other hand, there are variants rather specific for some countries or regions; for example, c.342+1G4A (ivs5+1G4A) for Slovakia and the Czech Republic, 9 c.87+1G4A (ivs2+1G4A) for the gypsy community Narikuravar in India 10 or c.360T4G (p.(Cys120Trp)) for the Dominican Republic. 11 So far, about 950 AKU patients have been reported in 61 countries worldwide (AKU Society, www.akusociety.org).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Some of the reported HGD variants are spread throughout the world, such as c.175delA (p.(Ser59Alafs*52)), one of the first identified AKU mutations, c.899T4G (p.(Val300Gly)). 7 On the other hand, there are variants rather specific for some countries or regions; for example, c.342+1G4A (ivs5+1G4A) for Slovakia and the Czech Republic, 9 c.87+1G4A (ivs2+1G4A) for the gypsy community Narikuravar in India 10 or c.360T4G (p.(Cys120Trp)) for the Dominican Republic. 11 So far, about 950 AKU patients have been reported in 61 countries worldwide (AKU Society, www.akusociety.org).…”
Section: Introductionmentioning
confidence: 99%
“…12 This country and the Dominican Republic exhibit prevalence of AKU of up to 1:19 000. 13,14 Recently, a high number of AKU cases were also found in Jordan 15 and India, 10 indicating that the overall prevalence of this disease in some countries might be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…All variants are summarized in the HGD mutation database (13-15). p.R58fs is one of the first identified AKU mutations (16)(17)(18)(19). At the same time, there are variants rather specific to some countries or regions.…”
Section: Discussionmentioning
confidence: 99%
“…Slovakia and the Dominican Republic exhibit a prevalence of AKU up to 1:19 000 (21,22). Recently, a high number of AKU cases were also found in Jordan (23) and India (18). Nemethova et al (24) reported 99 AKU patients with 12 novel mutations from Italy.…”
Section: Discussionmentioning
confidence: 99%
“…AKU is very rare in most ethnic groups (one in 250,000-1,000,000), but in some countries, such as Slovakia and recently Jordan and India, it exhibits increased prevalence. [13][14][15][16] Thanks to the work of patient organizations, effectively coordinated by the AKU Society, many new patients have been discovered. A new overview map has recently been created that reports 1,233 AKU patients worldwide ( Figure 2, courtesy of AKU Society, Ciaran Scott).…”
Section: Genetics Of Aku and The Hgd Mutation Databasementioning
confidence: 99%